Improvement in glycaemic control in paediatric and young adult type 1 diabetes patients during COVID-19 pandemic: role of telemedicine and lifestyle changes. - Lazzeroni, Pietro; Motta, Matteo; Monaco, Sara; Laudisio, Serena Rosa; Furoncoli, Daria; Maffini, Valentina; Rubini, Monica; Tchana, Bertrand; Ruberto, Claudio; Dodi, Icilio; Iovane, Brunella (Acta Biomedica Atenei Parmensis, 2021)
Background and aim: COVID-19 pandemic determined a profound impact in everyday life and in routine follow-up of patients with type 1 diabetes (T1D). In this context, telemedicine represented an important tool to guarantee a regular care for these patients. Aim of our work was to assess metabolic control before and after lockdown in the cohort of T1D patients followed-up by our Service, to evaluate the impact of restrictive measures and of disease management through telemedicine.Methods: This is a retrospective observational study. Subjects were enrolled among children, adolescents and young adults affected by T1D and followed at the Regional Paediatric Diabetology Centre of the University-Hospital of Parma, Italy. We collected data about age, gender, ethnicity, anthropometric measurements, duration of disease, type of blood glucose monitoring used, type of insulin administration, daily insulin requirement and metabolic control, assessed using capillary HbA1c.Results: We enrolled 139 patients, mean age 13.9 years. During lockdown, we reported significantly more contacts through telemedicine between patients and medical team. Global glycol-metabolic control significantly improved, without differences in daily insulin requirement. Patients with a previous poor-controlled diabetes showed a greater improvement. Finally, mean weekly hours of physical activity decreased significantly, without worsening in BMI z-score.Conclusions: Our results show a global improvement in mean HbA1c, with a stronger result for patients with a previous non satisfactory control. In our setting, despite regulatory rules and physical and logistic limitations related to pandemic, no worsening of metabolic control has been shown for patients with type 1 diabetes.